Exploring the relationship between brand ambassadors and consumer purchasing behaviour - Walsh, Michael (The IIE, 2020)
This study aimed to look at the relationship between brand ambassadors and consumer purchasing behaviour in South Africa in relation to the footballing industry and the brands in the sports apparel industry. It found that there was a connection between the two areas in the study and was looked at through a cross-sectional qualitative uni-disciplinary method that used non-probability convenience sampling as there was a gap in the available research. In the sample that was a part of this study the relationship between brand ambassadors and the consumer purchasing behaviour was that brand ambassadors did have a role to play in their overall purchasing behaviour but was not the only deciding factor that was considered. Other factors were price, quality, fit and style. The sample in this research could be seen as having strong ties to their chosen team but can change the individual brand ambassadors they follow more frequently. An ambassador is only effective if the participant feels a personal connection to that ambassador. Longevity of success as a brand ambassador could only be found in football’s most successful player like Messi and Ronaldo being mentioned by almost all of the participants.
Keywords: Soccer; Sports industry; Team sports; Sports apparel; Messi, Lionel - Argentine footballer; Ronaldo, Cristiano - Portuguese footballer